**(i) (0, 2)**

Putting x = 0 and y = 2 in the L.H.S of the given equation,

x − 2y = 0 − 2×2 = − 4 ≠ 4

L.H.S ≠ R.H.S

Therefore, (0, 2) is not a solution of this equation.

**(ii) (2, 0)**

Putting x = 2 and y = 0 in the L.H.S of the given equation,

x − 2y = 2 − 2 × 0 = 2 ≠ 4

L.H.S ≠ R.H.S

Therefore, (2, 0) is not a solution of this equation.

**(iii) (4, 0)**

Putting x = 4 and y = 0 in the L.H.S of the given equation,

x − 2y = 4 − 2(0)

= 4 = R.H.S

Therefore, (4, 0) is a solution of this equation.